Broken homes and juvenile delinquency / Fong Yut Kuen - Fong , Yut Kuen (1983)
This graduation exercise is a study involving a comparison between the delinquent boys and the non-delinquent boys to show the incidence of broken homes in juvenile delinquency. It also contains a chapter touching on other factors other than the broken home factor in juvenile delinquency. The delinquent boys are chosen from the Sarawak Boys Home, Kuching and the non-delinquent boys are from a secondary boys schools administered by the Social Welfare Ministry for delinquents between the age of 10 to 18 years old. This graduation exercise consists of five chapters. The introduction chapter describes the purpose of this study and its scope. Chapter I deals with the research procedure and the problems encountered during the fieldwork. The concepts of juvenile delinquency and broken home are described in chapter II. Chapters III and IV concentrates on the analysis of the data collected like the relationship between broken homes and juvenile delinquency and the extent of the incidence of broken homes in juvenile delinquency. The final chapter is the conclusion.